Identifying Uncertainty-Specific Health Information Seeking Practices in Orthopaedic Implant Patient Journeys - Charlotte Schrimpff; Tanja Fisse; Elena Link; Eva Baumann; Christoph Klimmt (European Journal of Health Communication (EJHC))
Uncertainty is an inherent part of illness that is assumed to vary over time. However, little is known about which kind of uncertainties occur during a chronic illness and how patients manage them at different times. To explore the dimensions of patients’ uncertainty perceptions and management strategies, such as health information seeking behaviour, over the course of the disease, we draw on uncertainty management theory and patient journey mapping. We conducted qualitative semi-structured interviews with 19 patients who had received a knee or hip replacement. We found distinct patterns of uncertainty perceptions related to physical, psychological, social/personal, and treatment-related issues in six different phases of the patient journey. Uncertainty perceptions were multi-layered and interconnected. We also found that uncertainty management strategies, such as information seeking, were highly targeted to the uncertainty at hand. Furthermore, our results revealed a high degree of context-specific uncertainty management strategies over the course of a patient journey.